The Safety and Efficacy of Single-Agent Pemetrexed in Platinum-Resistant Advanced Urothelial Carcinoma: A Large Single-Institution Experience. (6th April 2015) - Bambury, Richard M.; Benjamin, David J.; Chaim, Joshua L.; Zabor, Emily C.; Sullivan, John; Garcia-Grossman, Ilana R.; Regazzi, Ashley M.; Ostrovnaya, Irina; Apollo, Aryln; Xiao, Han; Voss, Martin H.; Iyer, Gopa; et al.
Abstract: Background: Pemetrexed is a commonly used treatment for platinum-resistant advanced urothelial carcinoma (UC) based on objective response rates of 8% and 28% in two small phase II studies. To address the discrepancy in reported response rates and to assess efficacy and toxicity outside of a clinical trial setting, we performed a large retrospective analysis of pemetrexed use at Memorial Sloan Kettering Cancer Center. We also investigated candidate prognostic factors for overall survival in this setting to explore whether the neutrophil-lymphocyte ratio (NLR) had independent prognostic significance. Patients and Methods: Patients receiving pemetrexed for platinum-resistant advanced UC between 2008 and 2013 were identified. The Response Evaluation Criteria in Solid Tumors (RECIST, version 1.1) were used to determine response rate. Kaplan-Meier and Cox regression analyses were used to examine the association of various factors with efficacy and survival outcomes. Hematologic toxicity and laboratory abnormalities were recorded. Results: One hundred and twenty-nine patients were treated with pemetrexed. The objective response rate was 5% (95% confidence interval: 1%–9%), and the median duration of response was 8 months. Median progression-free survival (PFS) was 2.4 months, and the 6-month PFS rate was 14%. There was no significant difference in response rate by age, Eastern Cooperative Oncology Group (ECOG) performance status, or number of prior therapies. On multivariable analysis, ECOG performance status ( p < .01), liver metastases ( p = .02), and NLR ( p < .01) had independent prognostic significance for overall survival. Conclusion: This 129-patient series is the largest reported data set describing pemetrexed use in advanced UC. Activity was modest, although discovery of molecular biomarkers predictive of response would be valuable to identify the small subset of patients who do gain significant benefit. Overall, the data highlight the urgent need to develop novel therapies for these patients. Abstract : This study presents the largest reported series of patients treated with pemetrexed. The results show that although well-tolerated, pemetrexed had limited efficacy. They also suggest a role for neutrophil-lymphocyte in the prognostication of advanced urothelial cancer, which may be relevant when constructing prognostic models in future studies. There is an urgent need to develop novel therapies for this lethal disease.